Adaptation of Different Compomers to Primary Teeth Cavities - Shetty, Sumanth M; Shetty, Rashmi G (Journal of Orofacial Research, 2012)
Background: Compomers remain the material of choice for restoration of primary teeth as they combine the best of GIC and composites. However, as it is a resinous material, attentionis focused on polymerization shrinkage causing gaps at restoration cavity interface. Gaps represent decreased efficacy of adaptation. Aim: To evaluate the marginal adaptation of compomers (Dyract, Compoglass, and F-2000) in class I and V cavities in primary molars. Materials and methods: Sixty noncarious primary molars were divided for three compomers (20), which were subdivided to two groups. Standard class I and V cavities (10 each) were prepared and restored. The cavity interface was examined and observations analyzed. The cavities were etched prior to restoration and margins were exposed. The cavosurface margins were inspected under stereomicroscope for surface gaps. Then buccolingually sectioned, they were examined for marginal gaps. Two specimens each were selected for SEM. Chi-square test was used to determine statistical significance (p < 0.05). Results: All compomers showed good adaptation at cavosurface, with class I better than V. Compoglass and Dyract were better adapted to cavity walls than F-2000. SEM revealed close interlaced adaptation of filling material to etched cavity. Conclusion: This study has shown that compomers provide good adaptation at cavity margins with compules (Compoglass and Dyract) being a better mode of dispensing than syringe tubes (F-2000). SEM showed gaps and pooling of adhesive and air in few samples.